ChemInform Abstract: Tailoring the S‐Selectivity of 2‐Succinyl‐5‐enolpyruvyl‐6‐hydroxy‐3‐cyclohexene‐1‐carboxylate Synthase (MenD) from Escherichia coli. Issue 16 (22nd April 2014) - Pohl, Martina; et al., et al.
Abstract S‐selective EcMenD variants of the thiamine diphosphate (TDP)‐dependent enzyme 2‐succinyl‐5‐enolpyruvyl‐6‐hydroxy‐3‐cyclohexene‐1‐carboxylate synthase from Escherichia coli (E.C.